2016
DOI: 10.1101/gad.289256.116
|View full text |Cite
|
Sign up to set email alerts
|

A role for mitotic bookmarking of SOX2 in pluripotency and differentiation

Abstract: Mitotic bookmarking transcription factors remain bound to chromosomes during mitosis and were proposed to regulate phenotypic maintenance of stem and progenitor cells at the mitosis-to-G1 (M-G1) transition. However, mitotic bookmarking remains largely unexplored in most stem cell types, and its functional relevance for cell fate decisions remains unclear. Here we screened for mitotic chromosome binding within the pluripotency network of embryonic stem (ES) cells and show that SOX2 and OCT4 remain bound to mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(244 citation statements)
references
References 60 publications
14
229
0
Order By: Relevance
“…UTF1, a chromatin-associated factor with histone-like characteristics (Kooistra et al, 2009; van den Boom et al, 2007), served as a positive control showing almost identical levels in asynchronous and mitotic chromatin extracts (Figures 1D–E). In agreement with recent studies (Festuccia et al, 2016; Teves et al, 2016; Deluz et al, 2016), this assay showed that SOX2, ESRRB and OCT4 as well as KLF4 were also highly retained on mitotic chromatin (ranging between 70–100% of respective levels in asynchronous cells). By contrast, factors such as NANOG and REX1 showed markedly reduced levels in the chromatin fraction during mitosis (Figures 1D–E).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…UTF1, a chromatin-associated factor with histone-like characteristics (Kooistra et al, 2009; van den Boom et al, 2007), served as a positive control showing almost identical levels in asynchronous and mitotic chromatin extracts (Figures 1D–E). In agreement with recent studies (Festuccia et al, 2016; Teves et al, 2016; Deluz et al, 2016), this assay showed that SOX2, ESRRB and OCT4 as well as KLF4 were also highly retained on mitotic chromatin (ranging between 70–100% of respective levels in asynchronous cells). By contrast, factors such as NANOG and REX1 showed markedly reduced levels in the chromatin fraction during mitosis (Figures 1D–E).…”
Section: Resultssupporting
confidence: 93%
“…This finding was surprising given that previously reported bookmarked targets by various TFs, including the recently described ESRRB and SOX2 in ESCs (Festuccia et al, 2016; Deluz et al, 2016), are often characterized by weaker binding during mitosis, suggesting either technical or biological differences between studies. To test the possibility that the strength of the detected signal in our mitotic samples was due to contamination from residual G2 cells (not more than 10% in our mitotic samples), we mixed interphase ESCs and neuronal progenitor cells (NPCs), which do not express KLF4, in a ratio of 10:90 and performed KLF4 ChIP-seq and ChIP-qPCR.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Both specific and non-specific binding sites on mitotic chromosomes were also observed for FoxA1 (77) where specific FoxA1 binding occurs at 15% of its interphase targets. Recently, Sox2 and Oct4 were also shown to remain bound during mitosis (78,79). In this last study, the authors also show using live imaging techniques that crosslinking with formaldehyde leads to eviction of most TFs from mitotic chromosomes.…”
Section: Stability Of Pioneer-induced Chromatin Remodelingmentioning
confidence: 59%